Knowledge, Attitude and Perception of Community Pharmacists in Kulim towards Preventing Medication Errors - Siti Nur ‘Aisyah Baharudin; Santhanathan A/L Rajendram; Shahnaz Majeed; Enrico Magosso; Sisinthy Sreenivas Patro; Ravindran Muthukumarasamy (Asian Journal of Medicine & Health Sciences, 2024)
Medication error falls under one of the five research priority domains identified by the Ministry of Health Malaysia in the Pharmacy Research Priorities. In Malaysia, there are some studies on medication errors, but most were done in hospitals. There is still no study on medication errors in community settings particularly in Kulim, Kedah. This study aimed to assess the knowledge, attitude and perception of community pharmacists in Kulim, Kedah regarding their role in preventing medication errors. This study is a cross-sectional survey, utilising an online questionnaire administered to community pharmacists in Kulim. Google Forms was used to generate and distribute survey questions. The sample size was estimated at 49 community pharmacists. , a Non-probability sampling was employed to gather data for this study. The self-administered questionnaire consists of four sections: 1) Section A: sociodemographic characteristics questions; 2) Section B: evaluation of respondents’ basic knowledge of medication errors; 3) Section C: evaluation of respondents’ attitude in preventing medication errors; and 4) Section D: evaluation of respondents’ perception towards roles in preventing medication errors. Among the 49 respondents, 48 (98%) demonstrated a good knowledge in preventing medication errors, with only 1 (2%) respondent showing fair knowledge. All respondents (100%) exhibited a positive attitude towards preventing medication errors. Forty-eight (98%) respondents have a good perception, with only 1 (2%) respondent had a fair perception. From the demographic data, only the highest education level has a significant association with the perception of respondents in preventing medication errors (p = 0.001). Community pharmacists in Kulim, Kedah exhibit good knowledge, positive attitude, and good perception toward preventing medication errors.